Assessing Nigeria’s journey towards IFRS adoption - Baba, Bello Usman (2013)
Recently the global corporate financial reporting scene has experienced a tremendous transformation with an unprecedented number of countries and enterprises around the world adopting IFRS as a basis in preparing financial statements.In Nigeria, the journey towards adoption of IFRS started in December 2010and thus an implementation roadmap was designed which was broken down into three phases. Based on the above affirmation, the studyassesses the achievements recorded so far, challenges being encountered, and measure taken in order to ensure a smooth and successful implementation of the threephases.Hence, the study is predominantly based on review of various journals,research papers,newspaper articles,periodicals and other documentary materials of professional accounting bodies as well as conferences, seminars and workshop papers.Consequently, the study found that most publicly quoted companies listed on the Nigerian stock exchange (NSE) were still far behind in their implementation process.Thus, the reason for the delay is attributed to several factors which ranges from challenge with amendment of the existing tax laws, the level of awareness among various stakeholders, weak compliance and enforcement mechanisms,the education level and experience, insufficient technical capacity,inadequate planning on the part of companies’ management as well as inadequate private sector participation.Accordingly, suggestions were made on how to forestall these challenges and ensure a smooth and successful implementation of the next phases.